Assessment of function of contractile segments in patients with left ventricular aneurysms by quantitative first pass radionuclide ventriculography. Haemodynamic correlation at rest and exercise. Issue 2 (February 1980) - Dymond, D S; Stephens, J; Stone, D; Jarritt, P H; Elliott, A; Britton, K E; Spurrell, R A
Abstract : Thirteen patients with left ventricular aneurysms complicating myocardial infarction were studied by contrast angiography and by first pass radionuclide ventriculography. The ejection fraction of the contractile segment (EFCS) was measured from both studies using a double hemishperoid model, and the values correlated closely. There was a monotonic relation between EFCS and stroke volume index measured from thermodilution cardiac outputs carried out simultaneously with the radionuclide study. When radionuclide ventriculography was performed at submaximal supine exercise, changes in EFCS paralleled changes in the total left ventricular ejection fraction in 10 of the 13 cases. In nine patients, changes in EFCS paralleled changes in stroke volume index and the relation between EFCS and stroke volume index was maintained at exercise. After administration of the vasodilator isosorbide dinitrate to 12 patients, repeat exercise radionuclide ventriculography showed an improvement in left ventricular ejection fraction and in eight patients EFCS improved. First pass radionuclide ventriculography can accurately estimate EFCS, which may be an important factor in predicting the likely response to aneurysmectomy. Changes in EFCS on exercise are reflected in changes in total left ventricular ejection fraction and stroke volume index. Isosorbide dinitrate may improve contractile segment function on exercise.